Studi Ekperimen: PENGARUH PROCEDURAL JUSTICE DAN DISTRIBUTIVE JUSTICE TERHADAP TINGKAT ESKALASI KOMITMEN DALAM PENGANGGARAN MODAL DENGAN SELF ESTEEM SEBAGAI VARIABEL INTERVENING - ANDI IRFAN (Solusi, 2020)
This study aims to discover and prove the influence of procedural dan distributivejustice on the level of escalation of commitmen with self esteem as intervening variable. This research uses student subjects Accounting in UIN SUSKA Pekanbar (55 peoples). This research design experiments in the form of 2 x 2 between subject. Before conducting actual experiments, this study conducted a pilot test to test the instruments used The hypothesis tested compiled using analysis of variance. Experiments carried out inf our stages 4 takes approximately 20 minutes.The results showed that a fair procedure in a company do not affect significantly the self esteem. A fair distribution of a company do not significantly qffectthe self esteem.. Hypothesis procedures and a fair distribution would have a positive effect on the self esteem to show the procedures and a fair distribution of a company do not affect significantly the self esteem. Then, self esteem is owned by each employee does not affect significantly the level of escalation of commitment. Key words: Self esteem, Justice, Procedual Justice, distributive Justice and escalation of commitment